2016
DOI: 10.1177/1474704916631213
|View full text |Cite
|
Sign up to set email alerts
|

Kin Investment by Step-Grandparents—More Than Expected

Abstract: Asymmetric grandparental caregiving is usually explained by the paternity certainty hypothesis. Accordingly, the lower investment by grandfathers (GFs) and paternal grandparents, as compared to grandmothers (GMs) and maternal grandparents, is based on differential kinship certainty to grandchildren. Hence, differential caregiving by grandparents is equated with their on-average different genetic relatedness to a grandchild. But what about nonbiological grandparents? All else being equal, step-grandparents shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 42 publications
6
25
0
Order By: Relevance
“…Aside from the effect of genetic relatedness on the size of monetary gifts, our study showed that matrilateral investment was greater than patrilateral investment, presumably because of differences in kinship assuredness (for other suggestions, see Pashos, Schwarz, & Bjorklund, ). The link between kinship certainty and investment is well established in evolutionary theory.…”
Section: Discussionmentioning
confidence: 58%
“…Aside from the effect of genetic relatedness on the size of monetary gifts, our study showed that matrilateral investment was greater than patrilateral investment, presumably because of differences in kinship assuredness (for other suggestions, see Pashos, Schwarz, & Bjorklund, ). The link between kinship certainty and investment is well established in evolutionary theory.…”
Section: Discussionmentioning
confidence: 58%
“…Several studies have indicated that males, due to paternity uncertainty, should rely more heavily on resemblance to children, as a cue of genetic relatedness, for investment decisions than females ( Daly & Wilson, 1982 ; Alvergne, Faurie & Raymond, 2009 ; Apicella & Marlowe, 2004 ; Platek et al, 2002 ; Burch & Gallup, 2000 ; McLain et al, 2000 ; Heijkoop, Dubas & Van Aken, 2009 ), but few have extended and investigated this prediction regarding grandparental investment (see, however, Euler & Weitzel, 1996 ; Schlee & Kirchengast, 2015 ; Pashos & McBurney, 2008 ). Also, putative relatedness weighted by certainty in relatedness, better predict willingness to invest in kin than putative relatedness alone ( Antfolk et al, 2017 ), and kin selection theory is also supported by studies comparing investments by grandparents and step-grandparents ( Pashos, Schwarz & Bjorklund, 2016 ; Gray & Brogdon, 2017 ). In fitness terms, grandparental investments can be viewed as an extension of parental investment, or as Euler & Weitzel (1996) points out, as a “differentiated subset of parental effort.” Consequently, investment decisions made by grandparents should be subjected to the same scrutiny as paternal investment decisions.…”
Section: Discussionmentioning
confidence: 92%
“…In total, the greatest grandchild investment is, therefore, by the maternal grandmother and the least grandchild investment by the paternal grandfather. This is the result not only of many empirical studies from evolutionary research (Bishop, Meyer, Schmidt, & Gray, 2009;Danielsbacka & Tanskanen, 2012;Danielsbacka, Tanskanen, Jokela, & Rotkirch, 2011;Euler & Weitzel, 1996;Kirchengast & Putz, 2016;Laham, Gonsalkorale, & von Hippel, 2005;Pashos, 2000;Pashos & McBurney, 2008;Pashos, Schwarz, & Bjorklund, 2016;Russell & Wells, 1987;Smith, 1988Smith, , 1991Steinbach & Henke, 1998) but also from the social sciences (Eisenberg, 1988;Hartshorne & Manaster, 1982;Hoffman, 1979Hoffman, /1980Lussier, Deater-Deckard, Dunn, & Davies, 2002;Matthews & Sprey, 1985;Monserud, 2008;Rossi & Rossi, 1990;Uhlenberg & Hammill, 1998;Van Ranst, Verschueren, & Marcoen, 1995). Other research studies, which directed their focus on aunts and uncles instead of grandparents, found a similar asymmetric pattern with highest kin investment by maternal aunts and lowest by paternal uncles (Gaulin, McBurney, & Brakeman-Wartell, 1997;Hoier, Euler, & Hänze, 2001;McBurney, Simon, Gaulin, & Geliebter, 2002;Pashos & McBurney, 2008).…”
Section: Asymmetric Caregiving By Grandparents and Aunts And Unclesmentioning
confidence: 97%
“…In a British survey, Dench and Ogg (2002) similarly interpreted stepgrandfathers to be more engaged with their new families compared with stepgrandmothers. In evolutionary terms, the stepgrandfathers' caregiving intention might be best explained by mating effort (Pashos et al, 2016). Good caregiving abilities appear to make men attractive marriage partners.…”
Section: Stepgrandparents: Nonconsanguineal Kin Caregiversmentioning
confidence: 99%